An unusual case of longest intussusceptum without any pathological lead point in an adult: A rare case report from a peripheral tertiary care institute of Eastern India - Manojit Sarkar; Rahul Dasgupta; Pintu Mudi; Nilima Shejole; Amit Ray (Asian Journal of Medical Sciences, 2024)
Bowel obstruction is known to be caused by intussusception, which is far more common in pediatric patients. The majority of people with adult intussusception require a predisposing cause, which might be a benign lesion, a malignant lesion, or an irregularity of the intestinal wall such as inflammatory bowel disease. Adult intussusception is a very rare condition. We present the case of a patient presenting with upper abdominal pain, nausea, vomiting, and weakness. The patient had ongoing mild intermittent abdominal pain for months which was investigated with an upper gastrointestinal endoscopy that showed gastritis. There were features of peritonism on clinical examination and this was associated with raised inflammatory markers. A contrast-enhanced multidetector computed tomography (MDCT) scan showed a long-segment telescoping of the ileum into the cecum with ascending colon with proximal bowel distension suggesting bowel obstruction: Ileocolic intussusception. The patient underwent emergency surgical resection with a double-barrel stoma. Histopathology assessment did not identify a causative factor for the intussusception. An uncommon instance of adult idiopathic enteroenteric intussusception is presented here. The diagnosis can be established with the use of the clinical history of chronic intermittent abdominal pain, entire abdomen ultrasonography, and abdomen MDCT. In patients who are unstable and exhibit indications of peritonitis, surgery remains the only choice, even though a more cautious strategy is outlined in the literature. Adult intussusception is a rare and challenging diagnosis to make. Individuals suffering from intussusception may experience prolonged bouts of sporadic abdominal pain that intensify suddenly as a result of acute obstruction. The most helpful investigative technique for confirming the intussusception diagnosis is CT.